Amatory pleasures : explorations in eighteenth-century sexual culture - Peakman, Julie, 1957- (Bloomsbury Academic, 2016)
"Encompassing the long 18th century, this reader examines a broad and enticing variety of topics in the history of sexuality in Georgian times. It includes discussion of sexual perversion, erotic gardens, gentlemen's secret societies, flagellation, pornography, writings of courtesans and the world of female friendship, revealing the secret or hidden meanings circulating between mainstream and covert activities of the 18th century. Including material previously available only in academic journals, revising these for a new readership and including two completely new chapters, Julie Peakman draws connections between these pieces and situates them within current debates. Her introduction examines how the covert life of Georgian sex was integrated from low life and high places, in brothels and palaces. Aimed at undergraduate and graduate students of gender, history of sexuality, sex literature and 18th-century history, Amatory Pleasures is an invaluable reader of the work of a key scholar in the field"--